Cupping for psoriasis vulgaris: A protocol of systematic review and meta-analysis - Zhang, Jie (Medicine (Baltimore), 2020)
BACKGROUND: Psoriasis vulgaris (PV) is a chronic, immune-mediated dermatological disease that significantly affects the patient's health and quality of life. At present, cupping has been widely used in the treatment of psoriasis. However, the effectiveness and safety of cupping in patients with PV are still controversial. Therefore, this review aims to evaluate the efficacy and safety of cupping therapy on PV. METHODS: The following databases will be searched from their inceptions to April 2020 with a language limitation of English and Chinese: Pubmed, Medline, Embase, Cochrane Central Register of Controlled Trials, Chinese Biomedical Literature Databas, China National Knowledge Infrastructure Database, Wanfang database and Chinese Scientific Journal Database. The reference lists of eligible studies and other resources will also be searched. Two researchers will independently perform the selection of studies, data extraction, and data analysis. A fixed or random-effect model will be applied to synthesize data depend on the heterogeneity test. The primary outcome is the proportion of patients achieving at least a 60% improvement in psoriasis area and severity index (PASI) score from baseline (PASI 60). Secondary outcomes include the proportion of patients achieving at least a 90% improvement in PASI score from baseline (PASI 90), the mean change of PASI and dermatology life quality index score, the itching index, adverse events, and recurrence rate. RevMan V.5.3 software will be used for meta-analysis. RESULTS: The study will provide a high-quality evidence-based review of cupping for PV. CONCLUSIONS: The study will be conducted to evaluate the efficacy and safety of cupping in the treatment of PV and supposed to provide clear evidence for the clinical application of cupping therapy. ETHICS AND DISSEMINATION: As the study is a protocol of systematic review and meta-analysis that does not involve individual data, ethical approval will not be required. The results will be published in a peer-reviewed journal. OSF REGISTRATION NUMBER: DOI 10.17605/OSF.IO/KV4CJ